Decoding Role-Based Access Control (RBAC) - Vinay Reddy Male (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article provides a comprehensive examination of Role-Based Access Control (RBAC) and its significance in modern cybersecurity, particularly within cloud environments. It explores the fundamental concepts of RBAC, including its core principle of assigning access rights based on organizational roles rather than individual users. The article delves into the implementation process, discussing role definition, permission assignment, and user-role association. It highlights the key advantages of RBAC, such as simplified permission management, enhanced security through the principle of least privilege, scalability in dynamic environments, and improved time efficiency in access management. A case study from the healthcare sector illustrates RBAC’s practical application, emphasizing its role in maintaining regulatory compliance and efficient operations in complex organizational structures. The article also addresses potential challenges in RBAC implementation, including role explosion and over-permissive access, and provides strategies for overcoming these issues through meticulous planning, regular audits, and ongoing system optimization. By offering insights into both the benefits and challenges of RBAC, this article serves as a valuable resource for organizations seeking to enhance their access control strategies in an increasingly complex digital landscape.